Mental health care use in medically unexplained and explained physical symptoms: findings from a general population study - van Eck van der Sluijs JF (Dove Medical Press, 2016)
Jonna F van Eck van der Sluijs,1,2 Margreet ten Have,3 Cees A Rijnders,4 Harm WJ van Marwijk,5,6 Ron de Graaf,3 Christina M van der Feltz-Cornelis1,2 1Clinical Centre of Excellence for Body, Mind and Health, GGz Breburg, 2Tranzo Department, Tilburg University, Tilburg, 3Netherlands Institute of Mental Health and Addiction, Utrecht, 4Department of Residency training, GGz Breburg, Tilburg, the Netherlands; 5Centre for Primary Care, Institute of Population Health, University of Manchester, Manchester, UK; 6Department of General Practice and Elderly Care Medicine, EMGO Institute for Health and Care Research, VU University Medical Centre, Amsterdam, the Netherlands Objective: The aim of this study was to explore mental health care utilization patterns in primary and specialized mental health care of people with unexplained or explained physical symptoms. Methods: Data were derived from the first wave of the Netherlands Mental Health Survey and Incidence Study-2, a nationally representative face-to-face cohort study among the general population aged 18–64 years. We selected subjects with medically unexplained symptoms (MUS) only (MUSonly; n=177), explained physical symptoms only (PHYonly, n=1,952), combined MUS and explained physical symptoms (MUS + PHY, n=209), and controls without physical symptoms (NONE, n=4,168). We studied entry into mental health care and the number of treatment contacts for mental problems, in both primary care and specialized mental health care. Analyses were adjusted for sociodemographic characteristics and presence of any 12-month mental disorder assessed with the Composite International Diagnostic Interview 3.0. Results: At the primary care level, all three groups of subjects with physical symptoms showed entry into care for mental health problems significantly more often than controls. The adjusted odds ratios were 2.29 (1.33, 3.95) for MUSonly, 1.55 (1.13, 2.12) for PHYonly, and 2.25 (1.41, 3.57) for MUS + PHY. At the specialized mental health care level, this was the case only for MUSonly subjects (adjusted odds ratio 1.65 [1.04, 2.61]). In both the primary and specialized mental health care, there were no significant differences between the four groups in the number of treatment contacts once they entered into treatment. Conclusion: All sorts of physical symptoms, unexplained as well as explained, were associated with significant higher entry into primary care for mental problems. In specialized mental health care, this was true only for MUSonly. No differences were found in the number of treatment contacts. This warrants further research aimed at the content of the treatment contacts. Keywords: medically unexplained symptoms, explained physical symptoms, mental health care use, general population